Pediatric Varicella-related Hospitalization in Turkey Between 2008 and 2018: Impact of Universal Single Dose Varicella Vaccine (VARICOMP Study) - Dinleyici, Ener Cagri; Kurugol, Zafer; Devrim, Ilker; Bayram, Nuri; Dalgic, Nazan; Yasa, Olcay; Arisoy, Emin Sami (Lippincott Williams and Wilkins, 2025)
Background: A single-dose varicella vaccine at 12 months of age was introduced to the National Immunization Program in February 2013 in Turkey. This study aimed to evaluate varicella-related hospitalization in children and the impact of a single-dose live attenuated varicella vaccine over the first 5.5 years of introducing a universal varicella vaccination. Methods: We analyzed data collected from the medical records of children <18 years old who required hospitalization due to varicella in 17 cities representing 50% of the childhood population in Turkey between 2008 and 2018. We calculated the rate of hospitalization for varicella per 100,000 children during the study period. The main objective of this study was to determine the yearly rate of hospitalization due to varicella and to compare these rates in the pre-vaccine and post-vaccine periods. The secondary objective was to compare demographic features, varicella-related complications, and outcomes between the pre-vaccine and post-vaccine periods. Results: A total of 4373 children (2458 boys and 1915 girls; 72.3% previously healthy) were hospitalized for varicella over a 10-year period, including 2139 children during the pre-vaccine period and 2234 children during the post-vaccine period. Overall, varicella hospitalization rates decreased significantly after the introduction of varicella vaccination [pre-vaccine vs. post-vaccine period; 3.79 vs. 2.87 per 100,000 per year; P < 0.001; odds ratio 0.75; 95% confidence interval 0.64-0.88]. The incidence of varicella-related hospitalization among children between 1 and 5 years of age was significantly lower in the post-vaccine era than in the pre-vaccine era, with a 60.2% decrease in hospitalizations (2.43 vs. 6.12 per 100,000 children; P < 0.001, odds ratio 0.39; 95% confidence interval 0.34-0.46). In both the <1-year and 6- to 10-year age groups, the incidence of varicella-related hospitalizations was similar in the pre-vaccine and post-vaccine periods. The incidence of varicella-related hospitalization was higher in the post-vaccine era among 11-15 years and >15-year-old groups (P < 0.01 and P < 0.05). The mean age was higher during the post-vaccine period than during the pre-vaccine period (P < 0.001). The absolute number of secondary bacterial infections (P < 0.01), respiratory complications (P < 0.01), and neurological complications (P < 0.001) was significantly lower during the post-vaccine period. The incidence of severe varicella was lower during the post-vaccine period than during the pre-vaccine period (P < 0.001). Conclusions: After 5.5 years of routine single-dose varicella vaccine use, we observed the impact of varicella vaccination on the incidence of varicella-related hospitalizations, especially in the target age group. However, we did not observe herd protection in the other age groups. The implementation of a second dose of the varicella vaccine in the National Immunization Program would help control disease activity. © 2025 Lippincott Williams and Wilkins. All rights reserved.
Keywords: chickenpox; complication; Turkey; varicella; varicella-related hospitalization